If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + -1) = 2(a + 1) Reorder the terms: 3(-1 + a) = 2(a + 1) (-1 * 3 + a * 3) = 2(a + 1) (-3 + 3a) = 2(a + 1) Reorder the terms: -3 + 3a = 2(1 + a) -3 + 3a = (1 * 2 + a * 2) -3 + 3a = (2 + 2a) Solving -3 + 3a = 2 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -3 + 3a + -2a = 2 + 2a + -2a Combine like terms: 3a + -2a = 1a -3 + 1a = 2 + 2a + -2a Combine like terms: 2a + -2a = 0 -3 + 1a = 2 + 0 -3 + 1a = 2 Add '3' to each side of the equation. -3 + 3 + 1a = 2 + 3 Combine like terms: -3 + 3 = 0 0 + 1a = 2 + 3 1a = 2 + 3 Combine like terms: 2 + 3 = 5 1a = 5 Divide each side by '1'. a = 5 Simplifying a = 5
| 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 | | 77-3x=33x+17 | | t+3+8(5+t)= | | X+6=0.5X-2 | | 11-9x=61-44x | | 3-28=5a | | 2x+35=5x+12 | | -114-8x=9x+22 | | 4(2X-7)=0 | | 9+5(t+1)+4t= | | 3x+7=-59-9x | | 10(2X-3)=8X | | 7(t+9)+5+t= | | 8t+(7+3t)4+2t= | | 4(X-1)=3(1-X) | | 7+9x=63+x | | 8t+7(7+3t)4+2t= | | 4x+30=11x-40 | | 11-7x=176-42x | | 4t+9+(2t+7)6= | | 7(3x-15)=4(5-x) | | 8x+7=4x+37 |